STROKE RATE (SR) AND STROKE LENGTH (SL) FREESTYLE SWIMMER INDONESIAN STUDENT PARTICIPANTS POPNAS 2009 - Tri Tunggal Setiawan (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2016)
Purpose of this study to identify patterns of stroke rate (SR) and stroke length (SL) freestyle swimmer Indonesian student participants popnas 2009.Subjectsdrawn from participants weekend sports student athletes nationwide pool of 2009 branches in Yogyakarta Special Region.The data retrieval performed 1 time for 4 days, namely in the afternoon during the final numbers, the first step taken pictures of each swimmer's time following the final number and then calculated the number of stokes rate and velocity.Results indicate that the length of sl in both female athletes and men in the freestyle show curve and the same pattern, namely the shorter distances shorter renangan sl and the further distance the longer renangan sl but with different figures, the number of sr freestyle results shows the range 19.98 to male athletes and female athletes at 23:31. results from this study suggest that the number and length sl sr in the freestyle with different distances and curve have the same pattern. Key words: stroke rate (SR) and stroke length (SL)